2020
DOI: 10.1177/1559325820973131
|View full text |Cite
|
Sign up to set email alerts
|

Whole Body Low Dose Computed Tomography Using Third-Generation Dual-Source Multidetector With Spectral Shaping: Protocol Optimization and Literature Review

Abstract: For decades, the main imaging tool for multiple myeloma (MM) patient’s management has been the conventional skeleton survey. In 2014 international myeloma working group defined the advantages of the whole-body low dose computed tomography (WBLDCT) as a gold standard, among imaging modalities, for bone disease assessment and subsequently implemented this technique in the MM diagnostic workflow. The aim of this study is to investigate, in a group of 30 patients with a new diagnosis of MM, the radiation dose (CT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Only one recent study ( 27 ) showed the possibility to perform WBLDCT with doses lower than those observed in our patient sample (average CTDI vol of 0.3 mGy and DLP of 52 mGy cm), with the use of a dual source CT with spectral shaping over a population of 30 patients; however, the authors did not provide information about the patients’ BMIs, which has a considerable impact on dose estimation.…”
Section: Discussionmentioning
confidence: 71%
“…Only one recent study ( 27 ) showed the possibility to perform WBLDCT with doses lower than those observed in our patient sample (average CTDI vol of 0.3 mGy and DLP of 52 mGy cm), with the use of a dual source CT with spectral shaping over a population of 30 patients; however, the authors did not provide information about the patients’ BMIs, which has a considerable impact on dose estimation.…”
Section: Discussionmentioning
confidence: 71%
“…The corresponding retrospective case–control study compared the WB scan protocols of a third- and second-generation dual-source CT scanner at 100 kV in a total of 60 individuals, and resulted in a reduction of the mean effective dose of 74%. A recently published study investigating 30 patients using spectral shaping and a third-generation dual-source multidetector CT scanner further improved the effective dose [ 41 ]. Other improvements in dose reduction may be achieved by deep convolutional neural networks that are trained to remove CT image noise in order to improve the image quality of ultralow-dose CT scans to appear similar to normal-dose CT scans [ 42 ].…”
Section: Whole-body Computed Tomography (Wbct)mentioning
confidence: 99%
“…23,24 Automated attenuation-based anatomical tube current (mAs) modulation CARE Dose4D (Siemens Healthineers) and automated attenuation-based tube voltage (kV) selection functionality CARE kV (Siemens Healthineers) were used for dose reduction and optimization. 25 Data were reconstructed with a third-generation Advanced Modeled Iterative REconstruction (ADMIRE, Siemens Healthineers) and a dedicated IBHC algorithm for the correction of the beam hardening that improved image quality using 3D forward projection and exploits an additional 2-compartment iodine/water model. ADMIRE was set at a strength level of 3 (range 1-5) with medium smooth reconstruction convolution kernel (Bv40).…”
Section: Dect Data Acquisitionmentioning
confidence: 99%